Calcium mimics the chemotactic effect of conditioned media and is an effective inducer of bone regeneration. - Rubén Aquino-Martínez; David G Monroe; Francesc Ventura (PLoS ONE, 2019)
Background After bone resorption, ions and degraded organic components are co-released into the extracellular space. Ions and growth factors, although different in their biological nature, induce a common and coordinated chemotactic effect. Conditioned media has been used successfully in bone regeneration by promoting endogenous cell recruitment. Likewise, calcium alone act as a paracrine chemotactic signal, inducing the host's undifferentiated progenitor cell infiltration into the implanted biomaterials. The aim of the present study was to compare the chemotactic effect of calcium and conditioned media in primary calvarial cells. Methods The chemotactic cell response was evaluated in vitro using an agarose spot and a wound healing assay. In addition, we used a calvarial bone explant model ex-vivo. The healing potential was also tested through an in vivo model, a critical-size calvarial bone defect in mice. For the in vivo experiment, cell-free calcium-containing or conditioned media-containing scaffolds were implanted, and MSC's seeded scaffolds were used as positive control. After seven weeks post-implantation, samples were retrieved, and bone regeneration was evaluated by μCT and histological analysis. Osteogenic gene expression was evaluated by qPCR. Results We found that chemotactic cell migration in response to either calcium or conditioned media was equivalent in vitro and ex vivo. Accordingly, μCT analysis showed that bone regeneration induced by the MSC's seeded scaffolds was similar to that obtained with cell-free calcium or conditioned media-containing scaffolds. Pre-treatment with SB202190, a highly selective p38 inhibitor, abrogated the chemotactic effect induced by conditioned media. In contrast, p38 activity was not essential for the calcium-induced chemotaxis. Moreover, BAPTA-AM treatment, a cytosolic calcium chelator, decreased the chemotactic effect and the expression of key osteogenic genes induced by calcium or conditioned media. Conclusion We show that calcium ions alone not only mimic the conditioned media chemotactic effect, but also induce an osteogenic effect similar to that produced by transplanted MSC's in vivo. Furthermore, the chemotactic effect induced by conditioned media is calcium and p38 dependent. The rise in cytosolic calcium might integrate the different signaling pathways triggered by conditioned media and extracellular Ca2+. This calcium-driven in situ bone regeneration is a promising and convenient alternative to promote endogenous cell recruitment into the injured bone site. This pre-clinical cell-free and growth factor-free approach might avoid the disadvantages of the ex vivo cell manipulation.